OPTIMASI PEMBUATAN KEFIR CAMPURAN SUSU SAPI DAN SUSU ALMOND - Jonatan Prasetya Rahaju, Joddi
Almond milk contains vitamin E, linoleic, and oleic acids. Mixture of cow's milk and almond milk potentially increase the antioxidant levels in kefir. Kefir uses kefir grains inoculum, containing lactic acid bacteria (LAB), acetic acid bacteria (AAB), and yeast. The quality of kefir can be influenced by the concentration of inoculum, fermentation time, and nutrition of the ingredients. Therefore, this study aims to: (1) determine the optimum concentration of kefir grains based on organoleptic tests; (2) determine the ratio of cow's milk: almond milk and the optimum fermentation time based on organoleptic tests; (3) determine the ratio of LAB:AAB:yeast in kefir milk and kefir grains; (4) determine the antioxidant activity of optimum kefir variation. Inoculum optimization with variation of 5; 7.5; 10% (w/v) was carried out on cow's milk every 6 hours for 36 hours, (temperature 27oC; initial pH 6.5; volume: 100 ml). Furthermore, ratio optimization of cow's milk: almond milk mixture was carried out, respectively 1:0; 3:1; 1:1; 1:3; 0:1, fermented using kefir grains 7.5% (w/v) under the same conditions. Microbial abundance was enumerated on GYCA (AAB), MRSA (LAB), PDA (yeast), and NA (total bacteria). Antioxidant activity was determined by DPPH scavenging assay. Based on the results of the study, the organoleptic index of cow's milk kefir with an inoculum concentration of 5; 7.5; 10% (w/v), respectively 4,5; 4,6; 4,3. The preference index for cow's milk: almond milk kefir (1:0; 3:1; 1:1; 1:3; 0:1), respectively 3,1; 3,0; 2,4; 2,1; 1,5 with 24 hours of fermentation. Cow's milk kefir grains had the abundance of total bacteria, LAB, AAB, yeast respectively at 24 hours, 8,2×109 CFU/g; 1,2×108 CFU/g; 5,0×108CFU/g; 2,6×107 CFU/g. In cow's milk kefir, two phases of microbial succession were observed, namely: an increase of LAB from the beginning to the 12th hour (2×108 CFU/mL) followed by an increase of AAB at the 12th to 18th hour (4×108 CFU/mL). In addition, an increase of yeast up to 18 hours (3,5×108 CFU/mL) was also observed. After 18 hours, growth has become stagnant. Kefir grains in cow's milk: almond milk mixture (3:1) had the abundance of total bacteria, LAB, AAB, yeast respectively at 24 hours, 2,5×109 CFU/g; 1,5×108 CFU/g; 4,3×107 CFU/g; 2,4×107 CFU/g. In cow's milk: almond milk mixture (3:1) kefir, 2 phases of microbial succession were observed, namely: an increase in AAB and yeast in the first 12 hours of fermentation with a final abundance of 9×107 CFU/mL. Followed by an increase in LAB (6×107 CFU/mL) at 12th to 30th hour indicated that kefir fermentation had not been completed. Fermentation increased the antioxidant activity of cow's milk kefir and cow's milk:almond milk mixture (3:1) kefir, with a rate of increase in antioxidant activity, respectively 0,83×10-3 g/mL.hour and 2,08×10-3 g/mL.hour; accordingly achieved antioxidant activity (IC50), respectively 0.40 g/mL and 0.47 g/mL. The conclusions of this study: the optimum concentration of kefir grains in cow's milk was 7,5% (w/v) with an organoleptic index of 4.6. Cow's milk: almond milk mixture (3:1) kefir fermented for 24 hours gave optimum results with a preference index of 3, with the ratio of LAB:AAB:yeast, respectively on kefir milk (1:2:3) and on kefir grains (6:2:1), and antioxidant activity (IC50) of 0,47 g/mL.